A companion to mysticism and devotion in northern Germany in the late middle ages - Andersen, Elizabeth (Elizabeth A.) (Brill's companions to the Christian tradition, 2013)
The volume explores the hitherto uncharted late medieval religious landscape of Northern Germany, from 13th-century Helfta to the 15th-century Lüneburg convents. The mystical and devotional writing of Northern Germany is contextualised through chapters on the Netherlands, Scandinavia and East Prussia. The seminal influence of the liturgy on these texts and their transmission is revealed in the creative interplay of Latin and Low German. Through the individual chapters and their appendices, which also contain translations into English, the reader can access a wealth of texts produced by communities of religious and lay women who write learnedly in Latin and fervently in Low German. Together, the chapters and appendices reveal a fascinating regional "mystical culture" which also reverberated across Northern Europe